Effectiveness of Transcranial Direct Current Stimulant in Major Depressive Disorder Patients: A Randomized Control Trial - Joomprabutra, Wireeon; Kongsuk, Thoranin; Aroonpongpaisal, Suwanna; Janthong, Supachai; Leejongpermpoon, Jintana; Saima-in, Hathairat; Sukhawaha, Supattra (Srinagarind Medical Journal, 2025)
Background and Objectives: Depressive disorder is related to abnormalities in the secretion of neurotransmitters in the brain. We study the effects of treating depression with transcranial direct current stimulation (tDCS) machine effect on depressive symptoms. Methods: a randomized, sham-controlled, double-blind trial (depressive disorder tDCS trial), conducted from May 2018 to December 2021. The participants were depressed patients with moderate symptoms and received antidepressants at Prasrimahabhodi Psychiatric Hospital, totaling 54 people. Randomized into experimental and control groups of 27 people per group, treated with tDCS and Sham, measured using the nine questions for depression (9Q) 6 times: after the end of therapy 15, 30, 45 days, 1, 2, and 3 years. Data were analyzed as an intent-to-treat analysis with the last observation carried forward (LOCF) method and recovery rate with survival analysis. Results: Immediately after the end of the therapy, 15 days, 30 days, and 45 days showed a greater decrease in the mean score of depressive symptoms in the tDCS group than the sham group, but no significantly different (p>.05). The rate of recovery from the evaluation with 9Q<7, tDCS group was 1.62 times higher than the sham group, but no significantly different (OR = 1.62, 95%CI 0.67-3.91, p>.05) Side effects in the first week found tingling at the stimulating area as 55.56%, headache as 22.2% and burning of the skin as 18.52%, and when followed for 1, 2, 3 years, it was found that the tDCS group had a chance of having a longer than recovery period than the sham group Conclusion: tDCS reduces depression in depressed patients with moderate symptoms. After the end of therapy 15 and 30 days, there were a few side effects. When following recovery for more than 3 years. However, this study was not statistically significant, which may be due to a small sample size. In the next study, a larger sample size should be determined.